1992
DOI: 10.1029/91ja02320
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of electron and ion precipitation in northern and southern polar regions for northward interplanetary magnetic field conditions

Abstract: Using the data of the DMSP F6 and F7 satellites, we show that there is a systematic difference between ion precipitation in the auroral oval and in the polar cap. The oval ion precipitation is smooth, and the ratio of the total electron number flux to the total ion flux is less than 20. The polar cap ion precipitation is patchy, and the ratio is more than 20. The boundary between these two types of ion precipitation usually can be detected for both northward and southward interplanetary magnetic field by a sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
2
12
1
Order By: Relevance
“…According to the above suggested classification, it is the boundary b3b between the AO and the SSSL where the auroral electron spectrum sharply softens. In reality, the spectrograms of all the DMSP satellite passes intersecting the dawn sector which have been presented in Troshichev and Nishida (1992) agree with this interpretation. According to this interpretation, the CPIP regime is nothing more than the SSSL regime.…”
Section: Summary and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to the above suggested classification, it is the boundary b3b between the AO and the SSSL where the auroral electron spectrum sharply softens. In reality, the spectrograms of all the DMSP satellite passes intersecting the dawn sector which have been presented in Troshichev and Nishida (1992) agree with this interpretation. According to this interpretation, the CPIP regime is nothing more than the SSSL regime.…”
Section: Summary and Discussionsupporting
confidence: 75%
“…Yet poleward of this boundary, the DMSP and Viking satellites observed not only intensive ion fluxes, but also intensive fluxes of auroral energy electrons as well. A detailed analysis of DMSP satellite data by Troshichev and Nishida (1992) showed that the TB really separates the highenergy electron region from the softer electron and ion precipitation region located further poleward. According to the above suggested classification, it is the boundary b3b between the AO and the SSSL where the auroral electron spectrum sharply softens.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The study of ion and electron characteristics measured by DMSP spacecraft [Troshichev and Nishida, 1992;Gusev and Troshichev, 1992] has shown that the region of regular auroral oval can be identified where the diffuse precipitation of ions E > 1 keV takes place, irrespective of IMF sign and level of magnetic activity. Intensity of ion flux can increase again in connection with spikes of electron precipitation observed inside the polar cap under the influence of the northward IMF, but the ratio of ion number flux to electron number flux in the polar cap turns out to be less than that in the regular oval.…”
Section: Identification Of the Polar Cap Boundarymentioning
confidence: 99%
“…Similarly, polar cap arcs have been reported as following a "teardrop" or "horse-collar" shape (that is, to be excluded from a central high latitude region) [Meng, 1981;Hones et al, 1989]. Others report that polar cap arcs can be found throughout the oval, interspersed with regions of polar rain or void [Hard), et al, 1982;Troshichev and Nishida, 1992]. This latter configuration is closely related to the 0 aurora, which consists of a brief IMF excursions can be highly geoeffective; for example, Greenwald et al [1990] found that 6 min after a change in IMF By reached the ionosphere, the entire radar field of view, 15 ø MLAT by 2.5 hours MLT near noon, had converted to the new convection configuration.…”
Section: Introductionmentioning
confidence: 99%